Sunno pyary bachoo - Khalid, Bazmi (Feroz sons Karachi, 1994)
This title suggests a narrative style where a character or narrator is directly addressing children. The story could be a moral tale, a folktale, or a simple adventure, intended to teach or entertain young listeners.